Swiss Household Energy Demand Survey (SHEDS): Objectives, design, and implementation - Sylvain Weber; Paul Burger; Mehdi Farsi; Adan L. Martinez-Cruz; Michael Puntiroli; Iljana Schubert; Benjamin Volland (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
The Swiss Household Energy Demand Survey (SHEDS) has been developed as part of the research agenda of the Competence Center for Research in Energy, Society, and Transition (SCCER CREST). It is designed to collect a comprehensive description of the Swiss households' energy-related behaviors, their longitudinal changes and the existing potentials for future energy demand reduction. The survey has been planned in five annual waves thus generating a rolling panel dataset of 5,000 respondents per wave. The first two waves of SHEDS were fielded in April 2016 and April-May 2017. This paper elaborates on SHEDS's general objectives, design, and implementation. It also reports a series of practical examples of how the datasets are being used in empirical analyses.
Keywords: Q40; C80; 330; energy; longitudinal survey; Switzerland